2006
DOI: 10.1177/000312240607100407
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood Social Processes, Physical Conditions, and Disaster-Related Mortality: The Case of the 1995 Chicago Heat Wave

Abstract: The authors draw on Klinenberg's (2002) ethnography and recent neighborhood theory to explain community-level variation in mortality during the July 1995 Chicago heat wave. They examine the impact of neighborhood structural disadvantage on heat wave mortality and consider three possible intervening mechanisms: social network interaction, collective efficacy, and commercial conditions. Combining Census and mortality data with the 1995 Project on Human Development in Chicago Neighborhoods Community Survey and Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
115
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(121 citation statements)
references
References 36 publications
5
115
0
1
Order By: Relevance
“…Based on a review of literature, we identified 20 census variables that have been used consistently to approximate neighborhood-level environments for possible inclusion in the deprivation index. These measures included the following * : one education variable, 47,48 two employment, 49,50 five housing, [51][52][53] four variables representing occupation, 10,54 five poverty, [55][56][57][58] one racial composition, 51,59 and two residential stability.…”
Section: Data Reduction and Exposure Definitionmentioning
confidence: 99%
“…Based on a review of literature, we identified 20 census variables that have been used consistently to approximate neighborhood-level environments for possible inclusion in the deprivation index. These measures included the following * : one education variable, 47,48 two employment, 49,50 five housing, [51][52][53] four variables representing occupation, 10,54 five poverty, [55][56][57][58] one racial composition, 51,59 and two residential stability.…”
Section: Data Reduction and Exposure Definitionmentioning
confidence: 99%
“…Social and economic factors have been shown to influence mortality during periods of excessive heat (Greenberg et al 1983;McGeehin et al 2001;Browning et al 2006). A logical next stage in the study of the effect of heat events on mortality in Washington State would be to consider socioeconomic factors that shape exposure to heat and mitigation of the effects of heat, in particular, race/ethnicity, income and occupation.…”
Section: Research Gaps and Recommendations For Future Researchmentioning
confidence: 99%
“…The groups at greatest risk include the following: children, due to slower adaptation during exercise (AAP 2000); the elderly, due to changes in the physiological ability to maintain normal body temperature (Borrell et al 2006;Basu et al 2005;CDC 2005); poor and socially isolated populations, due to less access to mitigation measures (Greenberg et al 1983;McGeehin et al 2001;Browning et al 2006); some urban dwellers, due to heat island effects and lack of vegetation (Grimmond and Oke 1999;DeGaetano and Allen 2002); outdoor laborers, due to extended exposures and lack of access to drinking water and shade (Greenberg et al 1983; WA Dept Labor and Industries 2008); people with chronic illnesses (e.g., diabetes, heart disease), due to increased vulnerability to sustained heat (Medina-Ramon et al 2006); and the mentally ill, due to behavioral factors and the effects of psychoactive medications (Kaiser et al 2001). …”
Section: Introductionmentioning
confidence: 99%
“…It is distinct from more traditional conceptualizations of social capital as an influence on behavior regardless of the number of social ties within the community (Sampson et al, 1997;Sampson et al, 1999). Supported though extensive 6 sociological and criminological literature, collective efficacy is the mechanism that links social structure (disadvantage, ethnic heterogeneity, and residential mobility) to neighborhood and individual-level outcomes such as crime and victimization (Browning et al, 2006;Bursik, 2006;Sampson et al, 1997). High levels of collective efficacy brings a number of benefits to a community, such as a decrease in crime and disorder, higher levels of supervision for children, lower rates of obesity, and wellbeing as a whole (Bursik & Grasmick, 1999;Nicholson & Browning, 2012;Sampson et al, 1999).…”
Section: Perceptions Of Collective Efficacymentioning
confidence: 99%